PENGARUH SAAT PEMBERIAN PGPRM (PLANT GROWTH PROMOTING RHIZOSPHERIC MICROORGANISM) TERHADAP PERTUMBUHAN DAN HASIL BUNCIS PERANCIS - Umul Aiman; Bambang Sriwijaya; Gilang Ramadani (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2015)
French beans are foodstuff from agricultural products that are useful, for nutrient sources that needs continue to increase to rise as cunsumed by the whole society, so it needs to be improved productivity, for example by the giving of PGPRM. This reseacrh aims to determine the most appropiate time when giving the PGPRM which give growth and yield the best french beans. This reseacrh was conducted at the experiment station Mercu Buana University Faculty of Agroindustri Yogyakarta, located in Gunung Bulu, Sedayu, Bantul, Yogyakarta in February-April 2015. This reseacrh uses a single factor experimental design with 4 treatments were arrenged in the field using a completely randomized design (CRD) with 3 replications, namely Giving PGPRM at the time of preparation of the seed; Giving PGPRM at the planting time; Giving PGPRM one week after planting; and Giving PGPRM during vegetative growth, given once a week. The results from the reseacrh showed that while giving PGPRM (Plant Growth Promoting Rhizospheric Microorganism) effect on growth and yield french bean, that giving PGPRM once a week at the vegetative stage of growth showed a better french beans and giving PGPRM in preparing french bean seeds provide results better.Keywords : French beans, PGPRM (Plant Growth Promoting Rhizospheric Microorganism), The exact timing of PGPR